MUQĀRANAH SEBAGAI METODE MENEMUKAN SHUDHŪDH PADA MATAN HADIS - H. Rajab; Rustina N. Rustina N. (Pascasarjana IAIN Ambon, 2020)
This study intends to explain shudhūdh and the method of understanding it in the hadith matn. It seems that the research on shudhūdh that has been done by scholars and hadith experts focuses more on the hadith sanad, and leaves the discussion of shudhūdh that is in the hadith matn. This research is a qualitative descriptive study by relying on literature sources. From the research conducted, it is found that shudhūdh is actually the causes that make a hadith matn considered odd because it violates other matn which is more numerous or stronger, after comparisons between all the narrations in that hadith. The hadith whose matn is considered odd is called the shādhdh hadith, while the matn hadith which is more numerous is called the hadith maḥfūż. Comparison between narrators in a hadith is known as the muqaranah method, which has been applied to the matn since the time of the companions of the Prophet. As for the shudhūdh that can make the hadith matn awkward is idrāj, which is an insertion from a companion narrator; iqlāb, namely the interchangeability of the position of a word or sentence in matn; ziyādah, namely the addition of words or sentences from thiqah narrators; iḍṭirāb, which is the discovery of several different matnas without being able to decide which one is stronger or weaker; and taḥrīf and taṣḥīf, namely the occurrence of changes in letters or readings in words or sentences in the matn.